ገበታ: የአየር ለውጥን መቋቋም ስለሚችሉ የተሻሻሉ የእንስሳት መኖ ቴክኖሎጂዎች የራዲዮ ፕሮግራም፡ ክፍል ሶስት - International Livestock Research Institute (International Livestock Research Institute, 2025)
This third broadcast from Debre Birhan on Fana FM 90.0 focused on the oat-vetch mixture, with farmers from North Shewa sharing its benefits for milk yield and animal weight, and experts detailing its cultivation, agro-ecology, and productivity for sustainable livestock production. This radio program series is produced by the CGIAR Sustainable Farming and Scaling for Impact (S4I) programs and Accelerating the Impact of CGIAR Climate Research for Africa (AICCRA), and the Technologies for African Agricultural Transformation (TAAT) projects.